2019
DOI: 10.1016/j.dendro.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Siberian spruce tree ring anatomy: imprint of development processes and their high-temporal environmental regulation

Abstract: Due to its advantages in terms of much longer cover period and less demanding measurements, wood anatomy of Picea obovata Ledeb. was offered as spatiotemporal proxy record for tracheid differentiation kinetics. In this study, external and internal regulation of earlywood-to-latewood transition and properties of latewood were considered. The values and interrelations between cell number, tree ring width, maximal and mean radial cell diameter, maximal cell wall thickness and position of the transition to thick-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 93 publications
2
19
0
1
Order By: Relevance
“…VSM relates environmental factors to daily cambial growth rates using a piecewise linear function Vaganov et al. (2011) to simulate annual ring widths and associated daily and cellular‐scale outputs that can be compared with finer‐scale characteristics of the annual ring (E. A. Babushkina et al., 2019; H. C. Fritts et al., 1991; Vaganov et al., 2006, 2011). The model calculates a daily relative growth rate (from 0 to 1, dimensionless) for temperature and soil moisture (itself a modeled function of precipitation, snowmelt, evapotranspiration, and soil drainage) and a minimization function causes cellular growth and division to be controlled by the most limiting environmental factor scaled by daylength.…”
Section: Methodsmentioning
confidence: 99%
“…VSM relates environmental factors to daily cambial growth rates using a piecewise linear function Vaganov et al. (2011) to simulate annual ring widths and associated daily and cellular‐scale outputs that can be compared with finer‐scale characteristics of the annual ring (E. A. Babushkina et al., 2019; H. C. Fritts et al., 1991; Vaganov et al., 2006, 2011). The model calculates a daily relative growth rate (from 0 to 1, dimensionless) for temperature and soil moisture (itself a modeled function of precipitation, snowmelt, evapotranspiration, and soil drainage) and a minimization function causes cellular growth and division to be controlled by the most limiting environmental factor scaled by daylength.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies we found significant climatic response in radial growth and wood anatomy of both species in the study area. Cell production and radial growth is limited mainly by soil water availability in May-June (positive correlations with precipitation and negative ones with temperature), latewood CWT has positive correlation with temperature in the end of summer [29,44,45].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of seasonal kinetics is important for identifying and understanding the external signal perception during xylem formation and its "recording" in the final tree-ring anatomical structure. In several of our works, it was clearly shown that morphometric parameters of tracheids perceive growth-limiting effects of climatic factors for short intervals during the growing season [28,29,30]. However, it is still unresolved which of the three phases of tracheid differentiation is the most sensitive to external influence [12,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In the books [22,23], many problems are considered, one way or another related to the problem of similarity. For example, in [24][25][26], the determination of similarity is necessary to construct a function of the dependence of the maximum density of the annual ring on the total ozone content (TOC) in the atmosphere and for further reconstruction of unknown TOC values from this function. This task of the so-called bioindication is very important, since the series of ring densities are very long, while the TOC values have been measured only since 1927, and it is still impossible to carry out a correct analysis for them.…”
Section: Overview Of Similarity Analysis Methodsmentioning
confidence: 99%